Investigation Actions Against Defamation Cases - hidayatullah wantu (Universitas Negeri Gorontalo, 2019)
Abstract: Acts of carrying out investigations to deal with defamation. In Indonesia, defamation is considered not by the traditions of the Indonesian people who still uphold eastern customs and culture. However, the lack of socialization of these regulations which causes ignorance of the insulting regulations that are carried out by many people today, which results in negative values from technological advances. The purpose of the research to be achieved is to find out how the role of investigators in dealing with defamation is. Keywords: Execution, Investigation, Defamation.